(untitled) (Scientific journal of the Fergana State University, 2025)
The article discusses the key aspects and concepts related to communication between representatives of different cultures. In the context of globalization and cultural diversity, understanding the specifics of such interaction becomes critically important for successful communication in various fields. The main theoretical approaches, including cognitive, social and linguistic models, are also analyzed. Special attention is paid to differences in cultural values, perception and interpretation of information that can influence the communication process. Barriers such as stereotypes and cultural shocks are discussed, as well as strategies to overcome them. In addition, the author examines modern research in the field of intercultural communication and their practical application. This material will be useful to specialists in the fields of linguistics, sociology, psychology, as well as to anyone interested in issues of intercultural interaction in the modern world.